The Incentives to Quit tobacco in Pregnancy (IQuiP) protocol: piloting a financial incentive-based smoking treatment for women attending substance use in pregnancy antenatal services - Amanda L Baker; Melissa A Jackson; Amanda L Brown; Gillian S Gould; Adrian J Dunlop (BMJ Open)
Introduction While tobacco smoking prevalence is falling in many western societies, it remains elevated among high-priority cohorts. Rates up to 95% have been reported in women whose pregnancy is complicated by other substance use. In this group, the potential for poor pregnancy outcomes and adverse physical and neurobiological fetal development are elevated by tobacco smoking. Unfortunately, few targeted and effective tobacco dependence treatments exist to assist cessation in this population. The study will trial an evidence-based, multicomponent tobacco smoking treatment tailored to pregnant women who use other substances. The intervention comprises financial incentives for biochemically verified abstinence, psychotherapy delivered by drug and alcohol counsellors, and nicotine replacement therapy. It will be piloted at three government-based, primary healthcare facilities in New South Wales (NSW) and Victoria, Australia. The study will assess the feasibility and acceptability of the treatment when integrated into routine antenatal care offered by substance use in pregnancy antenatal services.Methods and analysis The study will use a single-arm design with pre–post comparisons. One hundred clients will be recruited from antenatal clinics with a substance use in pregnancy service. Women must be <33 weeks’ gestation, ≥16 years old and a current tobacco smoker. The primary outcomes are feasibility, assessed by recruitment and retention and the acceptability of addressing smoking among this population. Secondary outcomes include changes in smoking behaviours, the comparison of adverse maternal outcomes and neonatal characteristics to those of a historical control group, and a cost-consequence analysis of the intervention implementation.Ethics and dissemination Protocol approval was granted by Hunter New England Human Research Ethics Committee (Reference 17/04/12/4.05), with additional ethical approval sought from the Aboriginal Health and Medical Research Council of NSW (Reference 1249/17). Findings will be disseminated via academic conferences, peer-reviewed publications and social media.Trial registration number Australia New Zealand Clinical Trial Registry (Ref: ACTRN12618000576224).